SARS-CoV-2 seropositivity among healthcare professionals in a rural state - Brianna Wright; Daniel Kang; Allison Schuette; Melissa A. Ward; Matthew D. Krasowski; Aaron M. Scherer; Daniel J. Diekema; Joseph Cavanaugh; Loreen Herwaldt (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract